Detection of dry rubber content in rubber cup lumps using electrical impedance spectroscopy - PHUANGSOMBUT, KAEWKARN; PHUANGSOMBUT, ARTHIT; TERDWONGWORAKUL, ANUPUN (The Indian Journal of Agricultural Sciences, 2020)
The objective of this research was to apply electrical impedance spectroscopy for the detection of the dry rubber content in Para rubber cup lump samples prepared from rubber latex. The samples were collected during 2017 from eastern region of Thailand. Half-cut samples were measured for electrical parameters. The dry rubber content (DRC) of each cup lump was calculated as the weight of the cup lump multiplied by the initial DRC of the latex. A prediction model was developed using a partial least squares regression technique. Results showed that the capacitance of the cup lumps tend to decrease with increase in the frequency and high rubber content in cup lumps was associated with higher capacitance.The prediction of the model was moderately accurate.